Prospects and challenges for the conservation of farm animal genomic resources, 2015-2025 - Bruford, Michael W.; Ginja, Catarina; Hoffmann, Irene; Joost, Stéphane; Orozco-terWengel, Pablo; Alberto, Florian J.; Amaral, Andreia J.; Barbato, Mario; Biscarini, Filippo; Colli, Licia; Costa, Mafalda; Curik, Ino; et al. (Frontiers in Genetics, 2015)
Livestock conservation practice is changing rapidly in light of policy, climate change and market demands. The last decade saw a step change in technological and analytical approaches to define, manage and conserve Farm Animal Genomic Resources (FAnGR). These changes pose challenges for FAnGR conservation in terms of technological continuity, analytical capacity and the methodologies needed to exploit new, multidimensional data. The ESF Genomic Resources program final conference addressed these problems attempting to contribute to the development of the research and policy agenda for the next decade. We broadly identified four areas related to methodological and analytical challenges, data management and conservation. The overall conclusion is that there is a need for the use of current state-of-the-art tools to characterise the state of genomic resources in non-commercial and local breeds. The livestock genomic sector, which has been relatively well-organised in applying such methodologies so far, needs to make a concerted effort in the coming decade to enable to the democratisation of the powerful tools that are now at its disposal, and to ensure that they are applied in the context of breed conservation as well as development.